Water user associations in northern Ghana: from institutional panacea to reality check - Acheampong, Ernest Nti; Venot, Jean-Philippe (2010)
Small reservoirs development in Ghana dates back to the post-independence era. Small reservoirs were meant at providing water for livestock, mitigating the impacts of recurrent drought, increasing food security, and reducing poverty. These small reservoirs are mostly located in Northern Ghana and have become an integral component of the communities they serve by supporting multiple livelihood strategies (livestock, fishing, irrigation and domestic use). In the mid-1990s and early 2000s, several donor-led development projects invested in rehabilitating and upgrading these small reservoirs through the inclusion of canal irrigation infrastructures. Most projects established water users associations (WUAs) that were aimed at ensuring sustainable management of the upgraded schemes. The underlying hypothesis was that local communities tend to have greater incentives than external actors to maintain their natural resources base. Organizing local farmers in a WUA would then increase their sense of ownership, leading to better performance of the system. Evidence from northern Ghana showed that WUAs have had mixed results. There is evidence of some WUAs having positive impacts. However, it is also clear that most WUAs fail to live up to expectation. This paper argues that the relative failure of WUAs is mostly due to the implementation approach that was adopted for their establishment during past development projects, specifically, the lack of attention given to the complex social fabric and the multiple actors and livelihood strategies that organized around small reservoirs. Past development projects re-iterated the model of ?technology transfer? but, this time, by promoting an ?institutional fix?. Government and donors should not only invest in infrastructure rehabilitation but also in soft components (organization, capacity, extension) that need to be embedded in the local social fabric.